2009
DOI: 10.2528/pierc09112102
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Uwb Hmsiw Bandpass Filter Based on Complementary Split-Ring Resonators

Abstract: A novel complementary split ring resonators (CSRR) is applied to realize a compact Ultra-Wide Band (UWB) bandpass filter based on half-mode substrate integrated waveguide (HMSIW) in this paper. Sharpened rejection skirts and widened upper stopband are achieved due to the two resonant frequencies of the proposed CSRR. Very good agreement is observed between measurement and simulation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…SIW is typically fed by a microstrip [8][9][10][11][12], however, for a thick substrate, a 50 Ω microstrip feed line will be very wide and would excite higher order modes with the potential to radiate. As an alternative, we have developed a grounded coplanar waveguide (GCPW) feed for a smoother transition [13,14].…”
Section: Design Of An Ultra Wideband Gcpw-to-siw Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIW is typically fed by a microstrip [8][9][10][11][12], however, for a thick substrate, a 50 Ω microstrip feed line will be very wide and would excite higher order modes with the potential to radiate. As an alternative, we have developed a grounded coplanar waveguide (GCPW) feed for a smoother transition [13,14].…”
Section: Design Of An Ultra Wideband Gcpw-to-siw Transitionmentioning
confidence: 99%
“…Various SIW power dividers have been studied like in [1,3], and [4] and relatively good results have been already reported. For example, Hao et al in [1,4] utilized a SIW binary feed network that showed an improved performance, but its 2.5 dB insertion loss is still relatively high and does not cover the entire X-band frequency range (8)(9)(10)(11)(12). Similarly, Yang et al [5] developed an 8 way SIW power divider, but its insertion loss is also relatively high (2.5 dB) over 9-11 GHz frequency band, but definitely there is still a room for further development.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, by using CSRRs, we can achieve high level of circuit miniaturization. Therefore, CSRRs have been utilized in different microwave and antenna applications [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are many techniques presented to design UWB BPF. For example, quad-mode resonator (MMR) [2,3], multilayer coupled structure [4,5], and cascaded low-pass/highpass filters [6] have been widely used to achieve UWB characteristics.…”
Section: Introductionmentioning
confidence: 99%